Um novo anuro da Formação Crato (Aptiano) e a ilustração paleontológica como ferramenta complementar à pesquisa - Silva, Jéssica Costa (2024)
The Araripe Sedimentary Basin is globally recognized as a valuable fossil-bearing deposit. Located in Nova Olinda Municipality, in the southern part of Ceará, Brazil, it is considered one of the largest and most important Cretaceous Lagerstätten in the world and stands out for its variety of well-preserved fossils. This study presents a new fossil anuran from the Crato Formation (Aptian) and uses Paleontological Illustration as a complementary tool for research and scientific dissemination. The phylogenetic analysis of the specimen revealed characters compatible with Neobatrachia, within the Hyloidea superfamily, which differs from other fossil anurans from the Crato Formation, already identified or recorded, by several anatomical traits, such as a narrow maxilla with pedicellate teeth, a vomer with a distinct tooth-bearing torus containing six teeth, nasals separated by the parasphenoid, a prominent ocular capsule, and shorter, more robust forelimbs than the humerus, a femur with a length similar to that of the tibia and fibula, with fused astragalus and calcaneus, digit IV longer than digits III and V, and the distal ends of the terminal phalanges being slightly curved and nodose. The discovery and identification of this specimen contribute to the understanding of the evolution and diversification of the Anura group during the Mesozoic, particularly in Gondwana, as well as the reconstruction of the evolutionary history of related taxa